2016
DOI: 10.2741/4420
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial anomalies driver to age associated degenerative human ailments

Abstract: Mitochondria play a fundamental role in regulating a variety of complex metabolic processes to maintain adequate energy balance for cellular existence. To orchestrate these functions, an undisturbed mitochondrial dynamics is imperative through a set of tightly guided mechanisms. Interference in key signature processes by several genetic, epigenetic and age-linked factors triggers mitochondrial dysfunction through decrease in mitochondrial biogenesis, reduced mitochondrial content, aberrant mtDNA mutations, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 142 publications
(173 reference statements)
0
4
0
Order By: Relevance
“…There are relatively few diseases caused directly by mitochondrial mutations or polymorphisms (38, 39). In most cancers mtDNA polymorphisms are not considered to be ‘drivers’ of tumorigenicity (38, 40, 41).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are relatively few diseases caused directly by mitochondrial mutations or polymorphisms (38, 39). In most cancers mtDNA polymorphisms are not considered to be ‘drivers’ of tumorigenicity (38, 40, 41).…”
Section: Introductionmentioning
confidence: 99%
“…In most cancers mtDNA polymorphisms are not considered to be ‘drivers’ of tumorigenicity (38, 40, 41). Rather, they are among many genes influencing disease susceptibility, progression and severity (4042).…”
Section: Introductionmentioning
confidence: 99%
“…OS is linked to several chronic conditions including cancer, cardiovascular diseases and neurodegenerative diseases [ 33 ]. Paraquat (PQ, 1,1′-dimethyl-4,4′-bipyridinium dichloride) is an environmental toxin and OS stimulant that is widely implicated in reactive oxygen species formation and mitochondrial dysfunctions [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that exposure in the parental generation is remembered and transmitted to unexposed future generations through gametes as a "memory" of the environment. Environmental and metabolic conditions during gestation may shape epigenetic reprogramming and may further influence the lifetime health of the child and the disease aetiology in offspring [ 87 88 89 ]. This illustrates that the intrauterine environment (nutrition, stress, and so on) has a vital effect on developmental programming, which, in turn, not only influences the germline (sperm or egg) in the foetus (F1) but also the germline of the foetus (F2) [ 90 ].…”
Section: Introductionmentioning
confidence: 99%